Safe reinforcement learning for multi-energy management systems with known constraint functions - Glenn Ceusters; Luis Ramirez Camargo; Rüdiger Franke; Ann Nowé; Maarten Messagie (Energy and AI, 2023)
Reinforcement learning (RL) is a promising optimal control technique for multi-energy management systems. It does not require a model a priori - reducing the upfront and ongoing project-specific engineering effort and is capable of learning better representations of the underlying system dynamics. However, vanilla RL does not provide constraint satisfaction guarantees — resulting in various potentially unsafe interactions within its environment. In this paper, we present two novel online model-free safe RL methods, namely SafeFallback and GiveSafe, where the safety constraint formulation is decoupled from the RL formulation. These provide hard-constraint satisfaction guarantees both during training and deployment of the (near) optimal policy. This is without the need of solving a mathematical program, resulting in less computational power requirements and more flexible constraint function formulations. In a simulated multi-energy systems case study we have shown that both methods start with a significantly higher utility compared to a vanilla RL benchmark and Optlayer benchmark (94,6% and 82,8% compared to 35,5% and 77,8%) and that the proposed SafeFallback method even can outperform the vanilla RL benchmark (102,9% to 100%). We conclude that both methods are viably safety constraint handling techniques applicable beyond RL, as demonstrated with random policies while still providing hard-constraint guarantees.